The Effect Of Good Corporate Governance On Firm Value With Financial Performance As An Intervening Variable (Empirical Study Of State-Owned Enterprises Listed On The Indonesia Stock Exchange For The Period 2019-2021) - Lanang Gumelar Dada; Tituk Diah Widajantie (Jurnal Ekonomi, 2024)
This study aims to obtain empirical evidence of the effect of good corporate governance, proxied by managerial ownership, on firm value, proxied by Tobin's Q, and financial performance, proxied by ROA, as an intervening variable. The subject of this research is a state-owned enterprise (BUMN) company listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. The sample for this study was selected using a non-probability sampling technique with a purposive sampling approach, resulting in a total of 71 samples of companies that met the specified criteria. The analytical technique employed in this study was path analysis, conducted using IBM SPSS Statistics 25 software. The study yielded the following results:(1) There is no effect of good corporate governance on firm value in BUMN companies listed on the IDX; (2) There is no effect of good corporate governance on financial performance in BUMN companies listed on the IDX; (3) There is no effect of financial performance on firm value in BUMN companies listed on the IDX; (4) There is an influence of good corporate governance on firm value through financial performance in BUMN companies listed on the IDX.